MSMEs and Fintech: A Comparison of Theory of Trying and Theory of Planned Behavior - Joko Rizkie Widokarti; Shine Pintor Siolemba Patiro; Sakina Nusarifa Tantri; Hety Budiyanti (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Objectives: This study aims at examining the factors that trigger the intention of MSMEs owners to use fintech. The theories used in this study are Theory of Planned Behavior (TPB) and Theory of Trying (TT). This study compares the abilities of TT and TPB in predicting MSMEs and investors’ intentions in Indonesia when they use fintech services.Methodology: The population in this study are MSME owners spread across Jakarta, Jogjakarta, Semarang, and Surabaya. The sample size in this study was 427 respondents. To collect the data, this study used a purposive sampling technique and a quantitative method through questionnaires. Structural Equation Modeling (SEM) with a two-stage approach is used to analyze the data.Finding: The results of this study shows that TT fits better than TPB to explain the MSME’s owners’ intentions and behavior in using fintech services.Conclusion: The conclusion of this study showed that attitudes, subjective norms, and perceived behavioral control are significant predictors of intention based on TPB. Furthermore, the results of this study support that social norms, frequency, and attitudes are significant predictors of intention in TT.